2007
DOI: 10.1364/oe.15.015603
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the broadband polarization properties of linear 2D SOI photonic crystal waveguides

Abstract: Both quasi-TE and TM polarisation spectra for a silicon-on-insulator (SOI) waveguide are recorded over (1100-1700)nm using a broadband supercontinuum source. By studying both the input and output polarisation eigenstates we observe narrowband resonant cross coupling near the lowest quasi-TE mode cut-off. We also observe relatively broadband mixing between the two eigenstates to generate a complete photonic bandgap. By careful analysis of the output polarisation state we report on an inherent non-reciprocity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…The premise of the device operation is as follows: from our previous work it was shown that cross coupling between TE and TM eigenstates within such photonic crystal waveguides is characterised by a regular beating across the entire telecommunications spectrum and beyond [3]. This can be readily observed at long wavelengths where only TM light propagates but can also be observed within the band edge of the TE transmission pass band.…”
Section: Device Fabrication and Characterisationmentioning
confidence: 99%
See 2 more Smart Citations
“…The premise of the device operation is as follows: from our previous work it was shown that cross coupling between TE and TM eigenstates within such photonic crystal waveguides is characterised by a regular beating across the entire telecommunications spectrum and beyond [3]. This can be readily observed at long wavelengths where only TM light propagates but can also be observed within the band edge of the TE transmission pass band.…”
Section: Device Fabrication and Characterisationmentioning
confidence: 99%
“…The recent application to bio-sensing [2] relied on the band edge of a silica photonic crystal waveguide. Whilst this has been effective, the steepness of the edge is sometimes difficult to fabricate and often the definition of the edge is unclear when polarisation is involved [3]. Even in the most simple linear photonic crystal waveguides fabricated in SOI platforms, the preferred technology for lower cost high density photonic integration, significant challenges remain in fully understanding such properties within even the simplest components, including line defect waveguides within a 2D lattice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical difference in polarisation transmission properties has generally driven a focus on fabricating single polarisation (quasi-TE) photonic chips, although more sophisticated designs enable consideration of both eigenstates [6,7]. In order to better understand the polarisation properties of such simple crystal structures, we recently carried out a comprehensive evaluation of the polarisation properties of these linear waveguides and showed evidence of significant cross coupling across the entire transmission bands of both quasi-TE and TM (henceforth labeled simply TE and TM) eigenstates [8]. We also reported highly localized polarisation conversion at the TE transmission band edge, principally arising from resonant dispersion and beating demonstrated experimentally and through numerical simulation [8], raising some questions as to the exact definition of this edge.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better understand the polarisation properties of such simple crystal structures, we recently carried out a comprehensive evaluation of the polarisation properties of these linear waveguides and showed evidence of significant cross coupling across the entire transmission bands of both quasi-TE and TM (henceforth labeled simply TE and TM) eigenstates [8]. We also reported highly localized polarisation conversion at the TE transmission band edge, principally arising from resonant dispersion and beating demonstrated experimentally and through numerical simulation [8], raising some questions as to the exact definition of this edge. These properties, which were supported by numerical simulation, raise significant questions on the role of dispersion even within single TE polarisation components and necessitate a review of how these components are to be utilized.…”
Section: Introductionmentioning
confidence: 99%